Effect Knowledge and Attitude with Behaviour of HPV Vaccination in Women of Reproductive Age - Budi Darmawan; Bismarck J. Laihad; Frank M. M. Wagey (Indonesian Society of Obstetrics and Gynecology, 2023)
To observe the association between knowledge and attitude towards HPV vaccination with the behavior towards HPV vaccination on reproductive woman in Indonesia. Methods: We conducted observational analytic study with cross-sectional design. The study was conducted in obstetric and gynecologic outpatient clinic in Prof. Dr. R. D. Kandou General Hospital, Manado Indonesia through July and August 2021. Reproductively active woman were included as the subject. Univariate and bivariate analysis were conducted in this study. Results: We included 364 reproductive woman. The majority of the subject were 20-35 year-old woman (50.8%) and were married (61.3%). The majority of the subject (72.8%) have received information about HPV vaccination. We found significant association between knowledge and attitude with the OR of 5.57 (p=0.00). Knowledge and attitude showed significant association with eagerness towards HPV vaccination. However, knowledge and behavior did not show any significant association towards HPV vaccination behavior. Conclusion: There is a significant association between knowledge and attitude of HPV vaccination with eagerness toward HPV vaccination in reproductive women in Indonesia. Keywords: behavior, HPV vaccination, knowledge, reproductive women. Keywords: behavior, HPV vaccination, knowledge, reproductive women. Abstrak Tujuan: Untuk mengetahui hubungan pengetahuan dan sikap terhadap perilaku vaksinasi HPV pada perempuan usia reproduktif di RSUP Prof. DR. R. D. Kandou, Manado. Metode: Penelitian ini merupakan penelitian analitik observasional dengan pengambilan subjek potong lintang. Penelitian dilakukan di unit pelayanan bagian Obstetri dan Ginekologi RSUP Prof. Dr. R. D. Kandou Manado pada Juli- Agustus 2021. Subjek penelitian merupakan perempuan usia reproduktif yang bersedia untuk mengikuti penelitian ini. Analisis data akan dilakukan secara univariat dan bivariat serta dilaporkan pada penelitian ini. Hasil: Penelitian ini mencakup 364 perempuan dengan usia produktif. Mayoritas subjek merupakan perempuan dengan usia 20-35 tahun (50,8%) dan sudah menikah (61,3%). Mayoritas subjek (72,8%) pernah mendapatkan informasi vaksinasi HPV sebelumnya. Hubungan antara pengetahuan dan sikap terhadap vaksinasi menunjukkan hasil yang signifikan (p=0,00) dengan OR 5,57. Pengetahuan dan sikap juga menunjukkan hubungan yang signifikan dengan kesediaan vaksin (p<0,05). Pengetahuan dan sikap tidak menunjukkan hubungan yang bermakna terhadap perilaku vaksin (p>0,05). Kesimpulan: Terdapat hubungan yang bermakna antara pengetahuan dan sikap dengan perilaku keinginan vaksinasi HPV pada perempuan usia reproduktif. Kata kunci: pengetahuan, perempuan usia reproduktif, sikap, Vaksinasi HPV.